Abdominal wall endometrioma presenting as a cystic abdominal wall mass: a case report and literature review. Issue 8 (26th August 2021) - Davis, Tyler; Moudy, Paige; Barghuthi, Lutfi; Abdelgawad, Mohamed; Ismael, Hishaam
Abstract: Endometriosis is classically defined as 'the presence of endometrial glands and stroma outside of the uterine cavity and musculature'. Although it most commonly occurs in the pelvis, various extrapelvic locations have been reported in the literature. There seems to be a strong association between abdominal wall endometriomas and previous surgical scars. In female patients presenting with a cyclically painful abdominal wall mass, a high index of suspicion for endometrioma must be maintained, especially in the setting of previous gynecologic surgery. Although there may be a role for medical management of symptoms, the most definitive treatment of an abdominal wall endometrioma appears to be wide local excision with negative margins. This paper presents a 39-year-old female with an extensive gynecologic surgical history presenting with a 6 × 6 cm cyclically tender abdominal wall endometrioma treated with wide local excision.